A UFSM no projeto Rondon: acesso web ao patrimônio documental arquivístico - Rodrigues, Camila Poerschke (2014)
This work presents a study about the description of fund of documents Coordenação do Campos Avançado de Roraima Projeto rondon and its subsequent diffusion. This research is justified because this documents comprehend a relevant period of the institutional history, reporting the activities made by students and teachers participants throughout the lifetime of the campus, since its implementation, until complete disabling of the unit. In this way, they are part of the documentary heritage of the institution. The study was built from the outlined objetives: analysis of the situation found with regard to the arrangement and preservation of documentary set; documentary arrangement s adequacy; set of documents s description; development of a research tool, an inventory, based in the Norma Brasileita de Descrição Arquivística and and dissemination of this information through the ICA-AtoM software. The research held is of applied nature and qualitative. With regard to the instruments for data collection, were used observation and document analysis, particularly the Projeto de Implantação do Campus Avançado, the Regulamento interno do Campus, besides the Regimento Geral da UFSM and others University s documents. The description of the set of documents was held concurrently with the documentary inventory s preparation, which is the product resulting from professional máster and is divided according to the NOBRADE s area, which were used in the documentation s description. Lastly, the informations arising from the description was made available to research in web through ICA-AtoM software. Were inserted in the tool the data referring to the documentary fund, its series and respective subseries. Thus, an important part of the documentary UFSM s heritage is being preserved and disseminated to society.